The Primary Responses of Murine Neonatal Lymph Node CD4+ Cells are Th2-skewed and are Sufficient for the Development of Th2-biased Memory - Becky Adkins; Yurong Bu; Vladimir Vincek; Patricia Guevara (Clinical and Developmental Immunology)
Exposure of neonatal mice to antigen often results in Th2-biased responses in later life. Examples of this Th2 tendency are (a) secondary antibody responses dominated by the Th2-associated IgG1 isotype and (b) Th2-mediated tolerance to alloantigens. We previously reported that neonates develop primary Th1 and Th2 function in the lymph nodes but exclusive Th2 primary splenic responses. Here, we have tested whether the Th2 bias of adults initially immunized as neonates is due to the early, primary Th2 polarization in the spleen. Surprisingly, removal of the spleen at birth had no affect on either IgG1-dominant secondary responses or the development of tolerance to alloantigens. Thus, neonatal lymph nodes are sufficient to generate Th2-biased function following neonatal antigen exposure. To understand how this could arise, we examined the primary Th1/Th2 responses of CD4+ lymph node cells. Unlike the balanced Th1/Th2 responses seen with total lymph node cells, the primary responses of isolated CD4+ cells were skewed to IL-4 producing function. These results suggest that the early development of Th2-dominant responses by lymph node CD4+ cells contributes substantially to the subsequent development of Th2-dominant memory in neonates.